Effect of mixture design approach on nutritional characteristics and sensory evaluation of steamed bread added rice flour - Tian, Shuangqi; Wei, Yichun; Chen, Zhicheng (Frontiers in Nutrition, 2022)
This study was designed to evaluate the effects of different rice nutrient compounds on steamed bread's nutritional characteristics and sensory evaluation. The mixture design approach was used to research the interactions between different rice flours and wheat flours on the sensory evaluation of steamed bread. The arginine content of different rice flours (long-grained rice, polished round-grained rice, and black rice) was higher at 44.19%, 21.74%, and 34.78% than that of the common wheat, respectively. When the added amount of mixed rice flours exceeds 15%, the steamed bread gradually reduces its elasticity, sensory score, and has a smaller specific volume. Rice is a widely consumed grain product, which provides energy and nutrients for more than half of humanity, especially in Asia. Different rice varieties have received increased attention from researchers for their high bioactive substances and other health benefits. The results of the current study provide a theoretical basis for the nutritional steamed bread and noodle industries to use different rice flour as an ingredient for enhancing or to improve the nutritional value of flour products.